Embalagem ativa de amido termoplástico/poli (butileno adipato-co-tereftalato) com incorporação de curcumina solúvel em água - Mücke, Naiara (2020)
The reactive extrusion technique has been shown to be efficient in the incorporation of bioactive compounds for application in films with active properties. Curcumin presents recognized antioxidant and antimicrobial potential and its application in active packaging has been investigated. However, due to its insolubility in water which compromises its applicability and effective action, the use of commercial forms of water-soluble curcumin (curcumin encapsulated in hydrophilic polymers) has been reported. The influence of the presence of modified curcumin (its water-soluble form -WSC, from English water-soluble curcumin) on the properties of materials produced by reactive extrusion has not been studied yet. The effect of curcumin application in its original form (hydrophobic character) in polymeric materials composed of blends of TPS (thermoplastic starch) and poly (butylene adipate-co-terephthalate) (PBAT) has already been studied. In this case, a reduction in the starch esterification reaction was observed during extrusion which impairs its compatibility with PBAT and consequently the mechanical properties of the material, depending on the presence of curcumin. Furthermore, when the material was applied in contact with chia oil curcumin migrated to it due toits hydrophobic character changing the sensory properties of the packaged product causing the oil to acquire yellow color. Thus, the objective of this study was to produce and characterize antioxidant films composed of a blend of thermoplastic starch (TPS) and PBAT added with commercial water-soluble curcumin WSC (0.05% -NC1 and 0.5% -NC2, % in relation to the total formulation mass) comparing them with the control (NC, without adding curcumin). The films were produced by reactive extrusion with starch, PBAT, glycerol and citric acid, added with curcumin (NC1 and NC2) and compared to the control (NC). They were characterized in terms of instrumental measurement of color, opacity, mechanical properties, humidity, solubility, water vapor permeability (WVP), morphology, crystallinity by X-ray diffraction, infrared spectroscopy (FTIR-ATR) and thermogravimetric analyzes. The incorporation of curcumin resulted in lower luminosity, greater yellowish-greenish tonality, however, did not affect the opacity of the films. The mechanical properties evaluated demonstrate that the films did not differ significantly (p> 0.05) in terms of resistance to changes in the WSC addition functions. However, the addition of WSC in the lowest concentration (NC1 0.05%) led to a reduction in elongation when compared to the control in contrast the NC2 formulation (0.5%) resulted in films with a higher percentage of elongation and a lower module value Young's indicating greater flexibility and less rigidity than the others. The NC2 formulation also exhibited more compact morphology (indicative of better compatibility between the components) and less crystallinity than the other film formulations corroborating the aforementioned results indicating a plasticizer effect caused by the WSC at 0.5% concentration. However, the increase in curcumin concentration resulted in an increase in the solubility and WVP of the films compared to the control due to the hydrophilic character of the WSC in addition to representing an indication of less esterification and reticulation of starch by citric acid in the reactive extrusion. The FTIR-ATR analysis confirmed the presence of ester bonds indicating that the esterification process was achieved but to a lesser extent in the NC2 samples confirming what was observed in the solubility and WVP analyzes. Thermogravimetric analyzes allowed the identification of three to four thermal events in the degradation process of the films, with the greatest mass losses associated with degradation of TPS and PBAT.